(untitled) (Research, Society and Development, 2021)
The morphometric analysis of the foramen magnum (FM) and occipital condyles (OC) is essential for the clinical understanding of certain conditions, to support anatomical studies, and their description is extremely valuable in forensic anatomy. Morphological and morphometric aspects of FM and CO were analyzed in 107 dry skulls. With a caliper, the anteroposterior (AD) and transverse (DT) diameters of each FM and anteroposterior (AP), mediolateral (ML) of the OCs were collected. The results are described as means for FM: DA in male and female skulls were: 36.11mm ± 2.55; 35.26mm ± 2.91; DT: 30.24mm ± 2.22, 29.8mm, respectively. OC in male skulls: AP right side 19.81mm, left side 20.43mm; ML on the right side 12.79mm, left side 12.64mm. OC in female skulls: AP right side 21.00 mm, left side 21.19 mm; distance ML right side 12.67 mm, left side 13.16 mm. The following FM morphology was identified: oval (59%), egg-shaped (8%), diamond (9%), circular (10%), hexagonal (5%) or irregular (7%); the pentagonal shape (0.9%) only in female skulls. It can be seen that the FM and CO results are in agreement with the literature (FM: oval shape predominates, with a significantly larger ML measurement in male skulls). It is noted that morphometric studies boost forensic anatomy and the clinical and surgical understanding of the conditions that encompass FM, therefore studies in this scope are essential.